2010
DOI: 10.1021/nn1000468
|View full text |Cite
|
Sign up to set email alerts
|

Template-Assisted Fabrication of Salt-Independent Catalytic Tubular Microengines

Abstract: A simplified template-assisted layering approach for preparing catalytic conical tube microjet engines based on sequential deposition of platinum and gold on an etched silver wire template followed by dicing and dissolution of the template is described. The method allows detailed control over the tube parameters and hence upon the performance of the microengine. The recoiling bubble propulsion mechanism of the tubular microengine, associated with the ejection of internally generated oxygen microbubbles, addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
202
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(208 citation statements)
references
References 13 publications
2
202
2
2
Order By: Relevance
“…Efforts in this area range from synthetic modifications on existing biomotors [1][2][3][4][5] to purely synthetic catalytic bimetallic nanomotors [5][6][7][8]. Motion of the synthetic motors has been achieved using a number of propulsion mechanisms including autodiffusiophoresis [9][10][11], autoelectrophoresis [6,7,[12][13][14], and bubble generation [15,16]. There are numerous reviews of motors and we point to Ebbens and Howse [17] for a general review of motors and to Paxton, Sen, and Mallouk [7] or Wang [18] for reviews of self-electrophoretic motors.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts in this area range from synthetic modifications on existing biomotors [1][2][3][4][5] to purely synthetic catalytic bimetallic nanomotors [5][6][7][8]. Motion of the synthetic motors has been achieved using a number of propulsion mechanisms including autodiffusiophoresis [9][10][11], autoelectrophoresis [6,7,[12][13][14], and bubble generation [15,16]. There are numerous reviews of motors and we point to Ebbens and Howse [17] for a general review of motors and to Paxton, Sen, and Mallouk [7] or Wang [18] for reviews of self-electrophoretic motors.…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8 Such bubble-propelled microengines thus display efficient propulsion in salt-rich environments due to electrocatalytic decomposition of hydrogen peroxide fuel. [9][10][11] Previous studies have also indicated the facile motion of polymer-based micromotors or rolled up microjets in various diluted (3-4 fold diluted) real-life media. [12][13][14][15][16][17][18] However, recent reports claimed that the movement of bubble-propelled Cu-Pt microengines is greatly hindered in various diluted real samples, and even completely stopped in highly diluted serum or seawater.…”
mentioning
confidence: 99%
“…Conversely, Pt metal has been shown to produce catalysts with lower activation energy than all other group VIII metals, 20 and nanostructured Pt nanoparticle (Pt-NP) nanowires have shown lower activation energies than Pt−Pd catalysts. 9 This superior performance makes Pt catalysts wellsuited for H 2 O 2 decomposition as demonstrated in a wide variety of small-scale applications including sensors/biosensors, 21−23 Pt-loaded stomatocytes, 24 tubular bubble thrusters or nanomotors/microengines, 25 and microelectromechanical system (MEMS) based thrusters. 26 PtNPs have been grown on a wide variety of substrates including highly conductive surfaces such as graphene, 27−29 carbon nanotubes (CNTs), 30,31 and graphene foam, 32 as well as nonconductive surfaces such as oxides (e.g., SiO 2 , aluminum oxide), 33 and paper/cellulose.…”
Section: ■ Introductionmentioning
confidence: 99%